PRINSIP-PRINSIP DEMOKRASI DALAM HADIS NABI: STUDI MAUDHU'I TENTANG MUSYAWARAH, KEADILAN, DAN AMANAH - Suaib Daulay; Ardiansyah Ardiansyah; Muhammad Nuh Siregar (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2025)
Democracy is a political system that places sovereignty in the hands of the people and emphasizes the principles of equality, justice, participation, and respect for human rights. Although the concept of democracy developed within the Western tradition, its fundamental values have long been present in Islamic teachings, both in the Qur’an and the hadiths of the Prophet Muhammad (peace be upon him). This article aims to examine issues of democracy from the perspective of hadith by exploring democratic principles contained therein, such as consultation (shūrā), justice (‘adālah), equality (musāwāh), trust (amānah), as well as the recognition and protection of human rights. This study is a library-based research employing a qualitative approach, using primary sources in the form of major hadith collections such as Ṣaḥīḥ al-Bukhārī, Jāmi‘ al-Tirmiżī, and Musnad Aḥmad, along with secondary sources including books and scholarly journals relevant to democracy and Islamic political thought. Data analysis is conducted using descriptive-analytical methods and a thematic (maudū‘ī) approach. The findings indicate that the leadership practices of the Prophet Muhammad (peace be upon him) and the teachings found in hadith embody democratic values that are ethical and substantive in nature, even though they are not always terminologically identical to modern democratic concepts. Principles of consultation, social justice, leadership accountability, and respect for human dignity constitute an important foundation for building a just and prosperous society. Therefore, the hadiths of the Prophet (peace be upon him) can serve as a normative basis for developing a form of democracy rooted in Islamic values and relevant to the context of nationhood and statehood in Indonesia.